TEACHER OPINIONS ON SEXUAL EDUCATION OF STUDENTS WITH INTELLECTUAL DISABILITY IN LATVIA - Laganovska, Egija; Kviese, Elīna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Sexual education plays an important role in preparing children and adolescents for a safe and productive life. Sex education provides not only knowledge about different types of sexual issues, or about common sexually transmitted diseases, unwanted pregnancies, sexual violence, but also personal identity, safety, love, intimacy and relationships.This study was conducted in order to examine the opinions of special education teachers working with adolescents with intellectual disabilities on sexual education. A descriptive study design was used. The authors designed a questionnaire to explore the opinions of 72 special education teachers in Latvia.The research results approved how crucial it is to provide opportunities to receive sexual education for adolescents with intellectual disabilities at school.